POTENSI HIJAUAN SEBAGAI PAKAN RUMINANSIA DI KECAMATAN BUMI AGUNG KABUPATEN LAMPUNG TIMUR - ., Afrizal; Sutrisna, Rudy; ., Muhtarudin (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study aimed to determine the forage production in agriculture field and plantantion based on theplanting extensive and to determine the capacity of animal in Bumi Agung District East LampungRegency.This study was conducted in January 2014 in Bumi Agung District East Lampung Regency. Thisstudy used survey method. The method used was method of purposive sampling. Study consisted ofprimary and secondary data. The primary data included all information about agriculture field,harvest extensive, forage production, forage waste produced, and processing of waste fromagriculture and plantation. The secondary data included information about potency of agriculture,plantation, and animal husbandry in Bumi Agung DistrictThe result of this study showed that the forage production based on dry matter as much as34.858.257,94 kg/year have the capacity of cattle as much as 10.611,34 AU and for goats as much as9.095,44 AU. The population of ruminants in Bumi Agung District in 2013 were 865 cattles and2.083 goats. If it was counted from the forage of the whole potency existed, so it could add 9.746cattles and 49.087 goats.